Guru dan Murid dalam Bingkai Etika: Menyongsong Pendidikan Berkarakter di Era Modern - Jefri Jefri; Sendi Sendi; Herlini puspika sari (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Modern education focuses not only on sharing knowledge but also plays a crucial role in shaping students' character and ethics. This study explores the role of ethics as the foundation of teacher-student relationships, the moral challenges of the digital age, and character education strategies as solutions. Using literature review and conceptual analysis, the study found that values ​​such as honesty, responsibility, politeness, and mutual respect are key to creating harmonious interactions in the learning environment. On the other hand, technological advances and cultural changes present challenges in the form of decreased empathy and the misuse of social media. Therefore, character education based on teacher role models, collaboration, and humanistic discipline needs to be developed. The study's findings emphasize the importance of balancing digital advancements with moral development in realizing ethical and civilized education. The study also reveals that, despite significant challenges facing educators in the digital age, they can utilize technology to support better character formation through an educational model that emphasizes ethics. The role of families and communities is also crucial in supporting this character education, fostering synergy between all parties in creating a generation with noble character.